(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study explores the implications of Value Added Tax (VAT) in the app-based economy, particularly focusing on online motorcycle taxi drivers (ojek online) in Medan City. With the rapid digitalization of transportation services, the tax system faces challenges in adapting to platform-based income structures. This research uses a qualitative method through in-depth interviews and documentation with drivers and stakeholders. The result indicates a lack of understanding among drivers regarding their tax obligations and VAT mechanisms, exacerbated by limited transparency from ride-hailing platforms. This study suggests the need for regulatory clarity, education, and a more inclusive tax policy model to ensure fair taxation in the digital economy.. Keywords: VAT, Digital Economy, Ride-Hailing, Tax Policy, Medan